The Formation and Development of the International Legal Protection of Cultural Property (Global Journal of Cultural Studies, 2022)
The article considers the formation and evolution of the international legal protection of cultural property from ancient times to the present. The purpose of the article is to identify the prerequisites and features of each historical period in the development of international law in the context of the international legal protection of cultural property, as well as to systematize the relevant international legal acts. The authors provide their own periodization of the development of international legal protection of cultural property. It is concluded that the initial stage of codification of the international legal protection of cultural property is directly related to the development of the rules and customs of warfare.